Pesma Apps as Android-based Integrated Applications for Mahasantri Pesma KH Mas Mansur UMS - Bisrul Khafid; Devi Afriyantari Puspa Putri (Khazanah Informatika, 2020)
Pesantren Mahasiswa Internasional KH Mas Mansur (Pesma) has a shuttle facility for everyone who lives there. However, the use of the shuttle is not optimal because the ordering procedure still uses manual techniques. It contrasts with the rapid development of industry 4.0 and the mission of Pesma to get digitalization. This paper describes the effort to improve Pesma shuttle bookings by developing an application. The application is built upon the Android Studio 3.5.1 platform and uses Firebase real-time database. The development method implements the System Development Life Cycle (SDLC), Waterfall. The research results in an application called “Pesma Apps” that can be used by staff and mahasantri. Testing the Pesma apps, we obtained sufficiently good results where the black box testing proves that all functions work well. A usability testing using SUS with 30 respondents produces a good result at the level of 72.6, which suggests that the application is accepted.